2019
DOI: 10.3329/bjz.v47i1.42023
|View full text |Cite
|
Sign up to set email alerts
|

Growth performances and bioaccumulation of heavy metals in Anabas testudineus (Bloch, 1792) cultured using different market feeds

Abstract: The study was conducted to determine growth performances and bioaccumulation of Cr, Cu, Cd, Pb and Ni in fish organs such as intestines, muscle and gills of study species after culturing them for twelve weeks by using different commercial fish feeds. The highest average daily gain (ADG, g/day) and specific growth rate (SGR; %/day) were found in fish fed quality feed and lowest values were found in the fish fed mega feed. Best feed conversion ratio (FCR) value was found in fish fed quality feed among five diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…According to Rajeshkumar and Li [ 22 ], there are two main ways heavy metals can bioaccumulate in fish; by direct consumption of water and feed through the digestive tract, and non-dietary routes across permeable membranes, such as muscle and gills. Fatema et al [ 57 ] reported the accumulation of heavy metals such as Pb, Cd, and Cr from commercial fish feeds in Bangladesh caused higher concentrations of heavy metal in fish than the permissible limits set by the FAO and WHO. The results of the present study revealed that almost all types of fish feed used in pangasius and tilapia farms were contaminated with heavy metals above the permissible limit.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rajeshkumar and Li [ 22 ], there are two main ways heavy metals can bioaccumulate in fish; by direct consumption of water and feed through the digestive tract, and non-dietary routes across permeable membranes, such as muscle and gills. Fatema et al [ 57 ] reported the accumulation of heavy metals such as Pb, Cd, and Cr from commercial fish feeds in Bangladesh caused higher concentrations of heavy metal in fish than the permissible limits set by the FAO and WHO. The results of the present study revealed that almost all types of fish feed used in pangasius and tilapia farms were contaminated with heavy metals above the permissible limit.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to shrimp feed include rice bran, wheat, fish, shrimp, soy, beef liver, silkworms, and earthworms that contain substantial levels of heavy metals [ 1 ]. In the fish feeds manufactured by some well-known companies of our country, Cr concentrations were measured at 8.21 mg/kg and 15.55 mg/kg, respectively[ 25 ]. Furthermore, the Cr ranged from 20.25 to 301.5 mg/kg in the starter, grower, and nursery fish feeds formulated by another feed company of Bangladesh[ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, HMs concentrations in seafood such as fish, shrimp, lobster, and crabs, as well as surface water and sediments, have been documented from Saint Martin Islandalong the Bay of Bengal [ [21] , [22] , [23] ]. In addition, some authors [ 1 , 8 , [24] , [25] , [26] , [27] ] have documented the HMs concentration in different commercial fish and shrimp feeds in Bangladesh. HMs in water, sediments and P .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation